Chronic Pain as a Hypothetical Construct: A Practical and Philosophical Consideration - Doleys, Daniel M. (Frontiers in Psychology, 2017)
Abstract: Pain has been defined by the International Association for the Study of Pain (IASP) as “an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage”. Chronic pain is usually described as pain that has persisted for 3-6 months and/or beyond the expected time of healing. The numerical pain rating (NPR) is the customary metric and often considered as a proxy for the subjective experience of chronic pain. This definition of pain (chronic) has been of significant heuristic value. However, the definition and the models it has spawned tend to encourage the interpretation of pain as a measurable entity and implies that the patient’s experience of pain can be fully comprehended by someone other than the person in pain. Several major models of pain have been scrutinized and found to propagate the notion of pain as a ‘thing’ and fall prey to biomedical reductionism and Cartesian (mind-body) dualism. Furthermore, the NPR does not appear to capture the complexity of chronic pain and correlates poorly with other clinically meaningful outcomes. It, and other aspects of the current notion of chronic pain, appear to be an extension of our reliance on the philosophical principles of reductionism and materialism. These and other shortcomings identified in the IASP definition have resulted in an increased interest in a reexamination and possible updating of our view of pain (chronic) and its definition. The present paper describes an alternative view of pain, in particular chronic pain. It argues that chronic pain should be understood as a separate phenomenon from, rather than an extension of, acute pain and interpreted as a hypothetical construct (HC). HCs are contrasted to intervening variables (IV) and the use of HCs in science is illustrated. The acceptance of the principles of nonlinearity and emergence are seen as important characteristics. The practical implications and barriers of this philosophical shift for assessment, treatment, and education are explored. The patient’s narrative is presented as a potential source of important phenomenological data relating to their ‘experience’ of pain. It is further proposed that educational and academic endeavors